2021
DOI: 10.1038/s41388-021-01791-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum chaperone GRP78/BiP is critical for mutant Kras-driven lung tumorigenesis

Abstract: Lung cancer is the leading cause of cancer mortality worldwide and KRAS is the most commonly mutated gene in lung adenocarcinoma (LUAD). The 78-kDa glucose-regulated protein GRP78/BiP is a key endoplasmic reticulum (ER) chaperone protein and a major pro-survival effector of the unfolded protein response (UPR). Analysis of the Cancer Genome Altas (TCGA) database and immunostain of patient tissues revealed that compared to normal lung, GRP78 expression is generally elevated in human lung cancers, including tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Those differential intracellular protein aggregations might affect the activation levels of downstream signals. This was further supported by the expression of ER stress markers, such as ER chaperones glucose-regulated protein 78 (GRP78), GRP94, and complement C3, [19][20][21] which were significantly induced by M59, R140, or R345 variants, but not by WT. This difference was also observed in other ER stress and UPR marker such as CALR 22 and ATF4.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Those differential intracellular protein aggregations might affect the activation levels of downstream signals. This was further supported by the expression of ER stress markers, such as ER chaperones glucose-regulated protein 78 (GRP78), GRP94, and complement C3, [19][20][21] which were significantly induced by M59, R140, or R345 variants, but not by WT. This difference was also observed in other ER stress and UPR marker such as CALR 22 and ATF4.…”
Section: Discussionmentioning
confidence: 85%
“…18,19 We then argued whether ER stress or unfolded protein response (UPR) can be activated by those EFEMP1 mutants. We assessed the RNA expression of selected markers of ER stress/UPR [18][19][20][21][22][23] using qPCR assay. As expected, compared to WT EFEMP1, the levels of RNA expressions for Glucose Related Protein (GRP) 78, GRP94, Calreticulin (CALR), and activating transcription factor 4 (ATF4), but not for C/EBP homologous protein (CHOP), were significantly increased in M59 (Figure 3E-I).…”
Section: Activation Of Er Stress/misfolded Proteins Response In Trans...mentioning
confidence: 99%
“…The in-vivo streptozotocin-induced diabetes mouse model also revealed that BIP repression induced the ER stress through the activation of CHOP and hyperphosphorylation of eIF2α. Previous studies have also shown that the knockdown of BIP increased the phosphorylation of eIF2α, and increased CHOP expression in both in-vitro and in-vivo models [29]. Inhibition or suppression of BIP could induce the compensatory mechanism by the upregulation of ER chaperones.…”
Section: Discussionmentioning
confidence: 89%
“…A study based on cell experiments found that the simultaneous inhibition of activated Cdc42-associated kinase (ACK1) and AKT inhibited the growth and migration of KRAS-mutant NSCLC cells, providing the premise for the clinical translation of ACK1 and AKT inhibitors either as monotherapy or with rational combination [ 128 ]. GRP78 haploinsufficiency is reported to inhibit KRAS G12D-mediated tumor progression and prolong survival, and it is a potential therapeutic target for KRAS-mutant lung cancer [ 129 ]. It has also been found that regenerating family member (REG4) is highly expressed in KRAS-mutant lung adenocarcinoma, and that silencing REG4 can inhibit cancer cell proliferation and genesis, making it a potential therapeutic target [ 130 ].…”
Section: Advances In Drug Resistance and Oncological Mechanisms Of Kr...mentioning
confidence: 99%